Adipose tissue from metabolic syndrome mice induces an aberrant miRNA signature highly relevant in prostate cancer development - Massillo, Cintia (2020)
Prostate cancer (PCa) remains an important public health concern in Western countries. Metabolic syndrome (MeS) is a cluster of pathophysiological disorders with increasing prevalence in the general population that is a risk factor for PCa. Several studies have determined that a crosstalk between white adipose tissue (WAT) and solid tumors favors cancer aggressiveness. In this work, our main goal was to investigate the interaction between WAT and PCa cells through microRNAs (miRNAs), in MeS mice. We developed a MeS-like disease model using C57BL/6J mice chronically fed with high-fat diet (HFD) that were inoculated with TRAMP-C1 PCa cells. A group of five miRNAs (mmu-miR-221-3p, 27a-3p, 34a-5p, 138-5p, and 146a-5p) were increased in gonadal WAT (gWAT), tumors, and plasma of MeS mice compared to control animals. Three of these five miRNAs were detected in the media from gWAT and TRAMP-C1 cell cocultures, and significantly increased in MeS context. More importantly, hsamiR- 221-3p, 146a-5p, and 27a-3p were increased in bloodstream of PCa patients compared to healthy donors. Using miRNA microarrays, we found that 121 miRNAs were differentially released to the coculture media between HFD-gWAT and tumor cells compared to control diet-gWAT and tumor cells. Target genes for the 66 most deregulated miRNAs were involved in common pathways, mainly related to fatty acid metabolism, ER protein processing, amino acid degradation, PI3K AKT signaling, and PCa. Our findings show for the first time a signature of five miRNAs as important players involved in the interaction between WAT and PCa in MeS mice. Further research will be necessary to track these miRNAs in the interaction between these tissues as well as their role in PCa patients with MeS.